Differential binding of chemokines CXCL1, CXCL2 and CCL2 to mouse glomerular endothelial cells reveals specificity for distinct heparan sulfate domains - van Gemst, J. J. (PLoS One, 2018)
INTRODUCTION: Proliferative glomerulonephritis manifests in a range of renal diseases and is characterized by the influx of inflammatory cells into the glomerulus. Heparan sulfate (HS) is an important (co-)receptor for binding of chemokines, cytokines and leukocytes to the endothelial glycocalyx, a thick glycan layer that covers the inside of blood vessels. During glomerulonephritis, HS in the glomerular endothelial glycocalyx plays a central role in chemokine presentation and oligomerization, and in binding of selectins and integrins expressed by leukocytes. We hypothesize that distinct endothelial HS domains determine the binding of different chemokines. In this study we evaluated the interaction of three pro-inflammatory chemokines (CXCL1, CXCL2 and CCL2) with mouse glomerular endothelial cells (mGEnC-1) in ELISA in competition with different HS preparations and anti-HS single chain variable fragment (scFv) antibodies specific for distinct HS domains. RESULTS: HS appeared to be the primary ligand mediating chemokine binding to the glomerular endothelial glycocalyx in vitro. We found differential affinities of CXCL1, CXCL2 and CCL2 for HS in isolated mGEnC-1 glycocalyx, heparan sulfate from bovine kidney or low molecular weight heparin in competition ELISAs using mGEnC-1 as a substrate, indicating that chemokine binding is affected by the domain structure of the different HS preparations. Blocking of specific HS domains with anti-HS scFv antibodies revealed a domain-specific interaction of the tested chemokines to HS on mGEnC-1. Furthermore, chemokines did not compete for the same binding sites on mGEnC-1. CONCLUSION: CXCL1, CXCL2 and CCL2 binding to the glomerular endothelial glycocalyx appears differentially mediated by specific HS domains. Our findings may therefore contribute to the development of HS-based treatments for renal and possibly other inflammatory diseases specifically targeting chemokine-endothelial cell interactions.